Association between Triglyceride - High Density Lipoprotein Ratio with Angiographic Severity of Coronary Artery Disease in Patients with Non-ST Segment Elevated Myocardial Infarction: Association between TG HDL ratio and CAD severity in NSTEMI (Cardiovascular Journal, 2024)
Background: Non-ST Segment Elevated Myocardial infarction (NSTEMI) is a potentially life-threatening condition. Dyslipidaemia is a major contributor of coronary artery disease (CAD) and TG/HDL-C ratio can be an important marker for the prediction of the extent of CAD. This study was aimed to find out the relation between TG/HDL-C ratio with severity of coronary artery lesion in NSTEMI patients.Methods: A total of 200 NSTEMI patients were included and classified into two groups on the basis of TG/HDL-C ratio: Group-A (TG/HDL-C ratio ≤4, n=100) and Group-B (TG/HDL-C ratio >4, n=100). Angiographic severity was measured by Gensini score in all the patients during the same hospital stay period. Relation between TG/HDL-C ratio and angiographic severity was evaluated.Results: Mean age of the study populations was 55.13±8.49 (years) with male predominance (75%). Hypertension, diabetes mellitus, dyslipidaemia and obesity were significantly higher in Group-B (p36 (AOR=7.98, 95% CI=4.0-15.91, p